Hostile media reporting and its effect on patient management behaviour of doctors who have not faced workplace violence - Kaur, Amandeep; Ghosh, Tandra; Ahamed, Farhad (International Journal Of Community Medicine And Public Health, 2021)
Media finds doctors as a soft target for all sorts of healthcare system failure. The hostile media reporting has demonized the medical profession and has forced doctors to adopt a more reserved attitude. The present study focuses on assessing the effect of media on patient management by the doctors who had not faced violence at the workplace. It was observed that as a consequence of unfavorable media reporting, prescribing of investigations, and referral and consultation liaison increased, whereas, handling of complicated cases by the doctors decreased. Therefore, even the doctors who have not faced any workplace violence are influenced by news of workplace violence against doctors and are adopting safer strategies in the management of patients.